Thermal response test : in situ measurements of thermal properties in hard rock - Gehlin, Signhild (Luleå tekniska universitet, 1998)
In-situ determination of thermal properties in bedrock is important for the sizing of larger BTES systems. In-situ values of thermal conductivity may reduce required borehole length up to 30%. This thesis treats a new mobile thermal response test equipment (TED), developed in Luleå, Sweden, 1995-98. TED is set up on a small trailer, and is tried out on groundwater filled boreholes, fitted with single and double U-loop piping. It has been used at several commercial borehole direct cooling systems for telephone switching stations in Sweden, and on test-holes in a well documented closed down heat store in Luleå. The response tests show good accuracy and reliability of the measured thermal conductivity and thermal resistance provided good insulation of the equipment. The tests take into account the interaction of the bedrock with the duct piping and filling, the borehole geometry and groundwater and is a valuable tool for pre-investigations for BTES. Godkänd; 1998; 20070404 (ysko)